Frontotemporal thalamic connectivity in schizophrenia and schizotypal personality disorder. (June 2022) - Szeszko, Philip R.; Gohel, Suril; Vaccaro, Daniel H.; Chu, King-Wai; Tang, Cheuk Y.; Goldstein, Kim E.; New, Antonia S.; Siever, Larry J.; McClure, Margaret; Perez-Rodriguez, M. Mercedes; Haznedar, M. Mehmet; Byne, William; et al.
Highlights: We examined connectivity of the mediodorsal nucleus (MDN) and pulvinar. Groups included schizophrenia, schizotypal personality disorder (SPD) and controls. Frontal to MDN functional connectivity was comparable in SPD and controls. In SPD greater connectivity was associated with less symptom severity. This pattern may be protective against psychosis in SPD. Abstract: Schizotypal personality disorder (SPD) resembles schizophrenia, but with attenuated brain abnormalities and the absence of psychosis. The thalamus is integral for processing and transmitting information across cortical regions and widely implicated in the neurobiology of schizophrenia. Comparing thalamic connectivity in SPD and schizophrenia could reveal an intermediate schizophrenia-spectrum phenotype to elucidate neurobiological risk and protective factors in psychosis. We used rsfMRI to investigate functional connectivity between the mediodorsal nucleus (MDN) and pulvinar, and their connectivity with frontal and temporal cortical regions, respectively in 43 healthy controls (HCs), and individuals in the schizophrenia-spectrum including 45 psychotropic drug-free individuals with SPD, and 20 individuals with schizophrenia-related disorders [(schizophrenia ( n = 10), schizoaffective disorder ( n = 8), schizophreniform disorder ( n = 1) and psychosis NOS ( n = 1)]. Individuals with SPD had greater functional connectivity between the MDN and pulvinar compared to individuals with schizophrenia. Thalamo-frontal (i.e., between the MDN and rostral middle frontal cortex) connectivity was comparable in SPD and HCs; in SPD greater connectivity was associated with less symptom severity. Individuals with schizophrenia had less thalamo-frontal connectivity and thalamo-temporal (i.e., pulvinar to the transverse temporal cortex) connectivity compared with HCs. Thalamo-frontal functional connectivity may be comparable in SPD and HCs, but abnormal in schizophrenia, and that this may be protective against psychosis in SPD.